(untitled) (Al-Qamar, 2025)
In any civilized society, the foundation of mutual love, dignified respect, sacrifice, and the stability of peace and security rests upon the sincere fulfillment of one another’s rights. Until such a value becomes deeply ingrained, no society can truly be considered a cradle of peace. The violation of rights does not merely lead to resentment and disputes; it often escalates to corruption, bloodshed, and even outright warfare. History bears witness that many great conflicts and devastating wars have arisen as a result of the denial of rights and acts of oppression. One of the distinctive features of Islam is that it commands every individual to fulfill the obligations upon them in their entirety, warning those who show negligence or heedlessness of severe consequences in both this world and the Hereafter. Among the various categories of human rights, the most delicate and sensitive is that which pertains to financial dealings, wherein honesty, transparency, and caution are indispensable. Even a slight breach of trust or negligence in such matters can lead to intense disputes between parties, eventually taking the case to the court of a judge, which in turn fuels enmity and hostility. According to Islamic law, if a debtor deliberately delays the repayment of debt, he is deemed an oppressor, and the rightful claimant is permitted to recover his due independently. However, if the debtor is genuinely in hardship, the Shariah strongly urges the creditor to grant additional time and show leniency. The jurists have meticulously examined which rights may be claimed directly by the rightful party and the wisdom behind such permission, and which matters necessarily require the intervention of a judge. The classical works of Islamic jurisprudence contain numerous examples and precedents on this subject. The present study offers a critical and analytical examination of these issues, with particular reference to the opinions of the jurists regarding non-fulfillment of financial obligations, as well as the modern legal and social contexts in which a rightful claimant must depend upon judicial adjudication to obtain what is due to them.